Intraindividual, intraspecific, and interspecific variation shapes natural selection and its detection in two convergently-evolved lizard species - Simone Des Roches; Max R. Lambert; Michaela S. Brinkmeyer; Jacqueline M. Howells; Andy Dettinger; Erica Bree Rosenblum (PLoS ONE, 2025)
Much of our understanding of how natural selection operates comes from studies of highly heritable traits presumed to vary little within individuals. Here we show that intraindividual (within-individual) phenotypic variation is an important source of intraspecific variation, shaping both natural selection and its detection in wild, open populations. We employed a multi-year capture-mark-recapture (CMR) study of two lizard species (Sceloporus cowlesi and Holbrookia maculata) at the ecotone between the white gypsum dunes at White Sands National Park and the surrounding dark Chihuahuan desert soils. Unlike many CMR studies examining selection on morphology, we measured individuals’ traits at each capture. We found that our inferences into which traits were under selection depended on which measurement instance we used (first, last, or median measurement of all measurements of a given trait), and, therefore, the degree of intraindividual variation within each trait. We present a contingency analysis to facilitate assessing when traits are under selection, when they are not, and when intraindividual variation complicates these inferences. Beyond these conceptual advances, our work has implications for the White Sands system, a model system for repeated evolution. In particular, both lizard species experience different selection regimes within the same ecotonal habitat, despite both showing convergent evolution in dorsal blanching on White Sands.